2018
DOI: 10.1136/neurintsurg-2018-014246
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Clinical utility of CFD for assessment of intracranial aneurysm rupture – a systematic review and novel parameter-ranking tool

Abstract: BackgroundIntracranial aneurysms (IAs) are vascular dilations on cerebral vessels that affect between 1%–5% of the general population, and can cause life-threatening intracranial hemorrhage when ruptured. Computational fluid dynamics (CFD) has emerged as a promising tool to study IAs in recent years, particularly for rupture risk assessment. However, despite dozens of studies, CFD is still far from clinical use due to large variations and frequent contradictions in hemodynamic results between studies.PurposeTo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…Zhou reported a lower mean WSS (p = 0.037) in ruptured cases and no significant difference in OSI [44], which agreed with the findings by Can and Du [43]. Liang developed a scoring system for a variety of indexes and showed that the highest score was found for aspect ratio, followed by aneurysm size, LSA, average WSS, size ratio, minimum WSS, flow complexity, and OSI, whereas a much lower score was found for maximum WSS [40]. Most importantly, geometric factors are better discriminators than hemodynamic factors.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Zhou reported a lower mean WSS (p = 0.037) in ruptured cases and no significant difference in OSI [44], which agreed with the findings by Can and Du [43]. Liang developed a scoring system for a variety of indexes and showed that the highest score was found for aspect ratio, followed by aneurysm size, LSA, average WSS, size ratio, minimum WSS, flow complexity, and OSI, whereas a much lower score was found for maximum WSS [40]. Most importantly, geometric factors are better discriminators than hemodynamic factors.…”
Section: Introductionsupporting
confidence: 85%
“…This article excluded studies with a small number of aneurysms and location-specific aneurysms; however, it included serial studies from the same laboratory (hereinafter referred to as serial studies), which were not common in previous systematic reviews [40,43,44]. Thus, we begin with comparisons with those reviews.…”
Section: Comparisons With Previous Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Although these observational studies have associated aneurysm size and shape with enhancement on HR-VWI, computational flow dynamics data have suggested that the increased turbulent blood flow within larger and more irregular aneurysms might induce contrast stagnation along the vessel wall and concomitant pseudo-enhancement ( figure 4). 26 on July 11, 2020 by guest. Protected by copyright.…”
Section: Aneurysm Wall Enhancement As An Indicator Of Aneurysm Instabmentioning
confidence: 99%
“…Hemodynamics characteristics have been suggested to play key roles in the initiation, development and rupture of IAs [14][15][16]. Various hemodynamic factors, including wall shear stress (WSS) and high oscillating shear index (OSI), are involved in IA development through regulating arterial wall remodeling [17][18][19].…”
Section: Introductionmentioning
confidence: 99%